2012
DOI: 10.1136/emermed-2012-201127
|View full text |Cite
|
Sign up to set email alerts
|

Preparedness to care for victims of violence and their families in emergency departments

Abstract: A lack of general preparedness in EDs to care for all victims of violence, regardless of gender and age, can lead to many patients not receiving appropriate care and treatment. To correct this there is a need to implement guidelines and routines about the care for victims of violence. Further research can shed more light on which measures are needed to improve quality of care for these patients and their families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
(22 reference statements)
0
14
0
Order By: Relevance
“…Four studies identified that staff education and continual professional development (CPD) were paramount in responding appropriately to cases of DVA within the ED environment (Campbell et al, 2001;McGarry & Nairn, 2014, Maina, 2009Ramsden & Bonner, 2002 as mental health conditions, requiring the HCP to use a range of communication skills to elicit responses and disclosure . Such communication skills for clinical enquiry are reported as aiding an improved response to care provision and better patient outcomes (Leppakoski et al, 2010;Ramsden & Bonner, 2002;Van der Wath et al, 2013), including DVA survivors and their families (Rahmqvist Linnarsson, Benzein, Arestedt, & Erlingsson, 2013). This latter Swedish study identifies that even with established DVA networks within the ED setting, policies on family support, where evident, relate to women and children as survivors and fail to incorporate support for male family members (Rahmqvist Linnarsson et al, 2013).…”
Section: Current Obstacles For Staff Working In Edmentioning
confidence: 99%
See 2 more Smart Citations
“…Four studies identified that staff education and continual professional development (CPD) were paramount in responding appropriately to cases of DVA within the ED environment (Campbell et al, 2001;McGarry & Nairn, 2014, Maina, 2009Ramsden & Bonner, 2002 as mental health conditions, requiring the HCP to use a range of communication skills to elicit responses and disclosure . Such communication skills for clinical enquiry are reported as aiding an improved response to care provision and better patient outcomes (Leppakoski et al, 2010;Ramsden & Bonner, 2002;Van der Wath et al, 2013), including DVA survivors and their families (Rahmqvist Linnarsson, Benzein, Arestedt, & Erlingsson, 2013). This latter Swedish study identifies that even with established DVA networks within the ED setting, policies on family support, where evident, relate to women and children as survivors and fail to incorporate support for male family members (Rahmqvist Linnarsson et al, 2013).…”
Section: Current Obstacles For Staff Working In Edmentioning
confidence: 99%
“…Such communication skills for clinical enquiry are reported as aiding an improved response to care provision and better patient outcomes (Leppakoski et al, 2010;Ramsden & Bonner, 2002;Van der Wath et al, 2013), including DVA survivors and their families (Rahmqvist Linnarsson, Benzein, Arestedt, & Erlingsson, 2013). This latter Swedish study identifies that even with established DVA networks within the ED setting, policies on family support, where evident, relate to women and children as survivors and fail to incorporate support for male family members (Rahmqvist Linnarsson et al, 2013).…”
Section: Current Obstacles For Staff Working In Edmentioning
confidence: 99%
See 1 more Smart Citation
“…In a qualitative study of female victims of intimate partner violence in Sweden, victims reported experiencing retraumatization, uncaring behaviour and suffering in meetings with health care professionals (Pratt-Eriksson, Bergbom and Lyckhage, 2014). One study of Swedish emergency departments found that very few had routines for identifying victims of violence, and none were prepared to care for male victims of violence (Linnarsson, Benzein, Arestedt and Erlingsson, 2013). A need for structural improvements both inside and outside the health care system to improve professionals' knowledge about resources for victims of intimate partner violence was pointed out in another Swedish study (Lawoko, Sanz, Helstrom and Castren, 2011).…”
Section: Health Care System's Response To Victims Of Interpersonal VImentioning
confidence: 99%
“…A lack of general preparedness, can lead to many patients not receiving appropriate care or treatment. The needed preparedness includes regulatory documents, written routines, organized education for personnel, delegation of specific responsibilities to staff, and information about continued support and care (Linnarsson et al 2013).…”
mentioning
confidence: 99%